The patterns of admixture, divergence, and ancestry of African cattle populations determined from genome-wide SNP data - Gebrehiwot, N.Z.; Strucken, E.M.; Aliloo, H.; Marshall, Karen; Gibson, John P. (Springer, 2020)
HumplessBos tauruscattle are one of the earliest domestic cattle in Africa, followed by the arrival of humpedBos indicuscattle. The diverse indigenous cattle breeds of Africa are derived from these migrations, with most appearing to be hybrids betweenBos taurusandBos indicus. The present study examines the patterns of admixture, diversity, and relationships among African cattle breeds.Data for ~ 40 k SNPs was obtained from previous projects for 4089 animals representing 35 African indigenous, 6 EuropeanBos taurus, 4Bos indicus,and 5 African crossbred cattle populations. Genetic diversity and population structure were assessed using principal component analyses (PCA), admixture analyses, and Wright’sFstatistic. The linkage disequilibrium and effective population size (Ne) were estimated for the pure cattle populations.The first two principal components differentiatedBos indicusfrom EuropeanBos taurus, and AfricanBos taurusfrom other breeds. PCA and admixture analyses showed that, except for recently admixed cattle, all indigenous breeds are either pure AfricanBos taurusor admixtures of AfricanBos taurusandBos indicus.The African zebu breeds had highest proportions ofBos indicusancestry ranging from 70 to 90% or 60 to 75%, depending on the admixture model. Other indigenous breeds that were not 100% AfricanBos taurus, ranged from 42 to 70% or 23 to 61%Bos indicusancestry. The AfricanBos tauruspopulations showed substantial genetic diversity, and other indigenous breeds show evidence of having more than one African taurine ancestor.Neestimates based onr2andr2adjshowed a decline inNefrom a large population at 2000 generations ago, which is surprising for the indigenous breeds given the expected increase in cattle populations over that period and the lack of structured breeding programs.African indigenous cattle breeds have a large genetic diversity and are either pure AfricanBos taurusor admixtures of AfricanBos taurusandBos indicus.This provides a rich resource of potentially valuable genetic variation, particularly for adaptation traits, and to support conservation programs. It also provides challenges for the development of genomic assays and tools for use in African populations.